Caracterização de produtos cárneos desenvolvidos com adição de farinha do sabugo de milho (Zea mays) - Ferreira, Sabrina Fagundes (2014)
Currently a large number of people are searching for a healthier lifestyle, with a balanced diet, choosing for foods with low levels of fats and sugars and fibers increments. Desirable due to their nutritional, functional and technological properties, the fibers can be used to increase the demand for agricultural products and byproducts as well as ingredients for the food industry. Corn is one of the cereals most produced and consumed in the world, generating millions of tons of residues annually, including the corn cob. Rich in fibers, the corn cob is also a source of nutrients and minerals. Rich in fibers, the corn cob is also a source of nutrients and minerals. One of the new trends of the meat industry is the formulation of differentiated meat products that contain beneficial substances or superior properties to those of the original products, being increasingly the offering of products artificially enriched with nutritional and functional properties. The objective of this study was to develop meat products as from of the elaboration of flour of the corn cob. Were formulated four treatments of cook sausage meat (mortadella), added of flour of the corn cob (2,22%, 3,70% and 5,20%) and four treatments of the hamburger (3%, 6% and 8%). The flour was characterized according to the physico-chemical, microbiological and functional analyzes showing a good performance for application in meat products. The mortadella and the hamburgers were characterized according to physical-chemical, microbiological, instrumental texture and sensory analysis. The mortadella showed satisfactory behavior in all analyzes, however the formulation containing 5,20% of the flour did not show satisfactory results for the sensory analysis. The hamburgers showed the highest percentage of income in cooking and better sensory acceptability having lower acceptance for formulation with 8% of the flour. The study of the application of this source of fiber of agricultural by-product in meat products, gains importance due to the numerous advantages that research generates, bringing benefits to the health of people, and for the industries as an alternative and cheaper source of dietary fiber.